Change your schedule, change your life : how to harness the power of clock genes to lose weight, optimize your workout, and finally get a good night's sleep - Kshirsagar, Suhas G; Seaton, Michelle D (Harper Wave, 2018)
"An eye-opening handbook from a leading Ayurvedic physician that blends cutting-edge science on "clock genes" with ancient eastern wisdom to help us understand how to harness the power of chronobiology to effortlessly lose weight, sleep better, exercise stronger, reduce stress, and boost our well being. "It's not you, it's your schedule." Does it sound like magic? It's not. We've all heard of circadian rhythms--those biological processes that give us jet lag and make us night owls or early birds. But few of us know just how profoundly these diurnal patterns affect our overall health. Bad habits like skipping meals, squeezing in workouts when it's convenient, working late into the night to maximize productivity and then trying to "catch up" on sleep during the weekend disrupt our natural cycles. A growing body of research on chronobiology reveals just how sensitive the human body is to these rhythms all the way down to the genetic level. Our "clock genes" control more than we realize, and small changes can make the difference between battling our bodies, and effortlessly managing weight, sleep, stress, inflammation, and more. Marrying ancient Ayurvedic wisdom with the latest scientific research, Dr. Suhas Kshirsagar's holistic step-by-step 30-day plan gives you the tools--and the schedule--you need to transform your life. With diagnostic quizzes to determine your specific mind-body type, you will learn to adapt you schedule for effortless wellness for life"--